Immunomodulator effect of Cnidoscolus aconitifolius leaves extract on CD4+ and CD8+ expression in Salmonella typhimurium-infected mice - Sholihatil Hidayati; Dhina Ayu Susanti; Rian Anggia Destiawan; Ahdiah Imroatul Muflihah; Rizka Handayani; Wima Anggitasari (Universitas Ahmad Dahlan, 2024)
Typhoid fever is a common health problem in the community caused by Salmonella bacteria. The incidence rate of this infection will increase if a person's immune system is weakened. Plant extracts have been widely studied for their role in various pharmacological effects, including immunomodulatory effects. Among the plants with the potential to be used as an immunomodulatory substance is Cnidoscolus aconitifolius. Cnidoscolus aconitifolius leaves extract (CAE) contains flavonoids related to immunomodulatory activity. This study intends to ascertain how administering CAE affects the expression of CD4+ and CD8+ in Babl/c mice that have been infected with Salmonella typhimurium bacteria. The study was started by preparing 70% ethanol extract from Cnidoscolus aconitifolius leaves. Immunomodulatory activity testing was carried out preparing 30 Babl/C mice as experimental animals. Six mouse groups (the treatment group, the negative control, the positive control, and the healthy control) were allocated at random by giving CAE doses of 100 mg/kgBW, CAE doses of 200 mg/kgBW, and CAE doses of 400 mg/kgBW. Induction was carried out by oral infection with Salmonella thypimurium bacteria. After 3 days the infected mice were treated orally once a day for 7 days. Evaluation of CD4+ and CD8+ expression was carried out using the flow cytometry method of the lymph organs. The data was analyzed using the anova test and then the SPSS for Windows tool was used to do the post hoc test (Tukey). The results showed that giving CAE at doses of 100 mg/kgBW, CAE doses of 200 mg/kgBW and CAE doses of 400 mg/kgBW could increase the expression ratio of CD4+ and CD8+. Conversely, administering 400 mg/kgBW of CAE produced noticeably different outcomes (p<0.05) from the negative control. This shows that the CAE has potential as an immunomodulatory agent that can improve immune function.